Kontekstualisasi Nilai-Nilai Pendidikan Islam Moderat Melalui Program Keagamaan dan Proyek Penguatan Profil Pelajar Pancasila (P5) Pada Siswa Di SMP Negeri 5 Bojonegoro - Fela Nafiyati; Muhammad Muizzudin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to explore the contextualization of moderate Islamic values in SMP Negeri 5 Bojonegoro through religious programs and the Pancasila Student Profile Strengthening Project (P5). The research employs a qualitative descriptive approach with data collected through interviews, observations, and documentation. The findings reveal that moderate Islamic values such as tolerance, justice, balance, deliberation, and openness are integrated into various school activities, particularly through the Religious Programs and P5 projects. These values are contextualized by adjusting learning content and approaches to the school's pluralistic environment, where students of diverse religious backgrounds interact harmoniously. The Religious Program promotes values of peace and inclusivity through joint worship, interfaith dialogues, and character-building activities. Meanwhile, P5 projects focus on real-life applications of tolerance and cooperation among students from different faiths and backgrounds. Supporting factors in this contextualization include the school’s status as a driving school, the commitment of school leaders and teachers, active parental involvement, and a conducive school culture. In contrast, inhibiting factors include limited time allocation, lack of resources, and differences in understanding moderate values among stakeholders. Overall, the study concludes that contextualizing moderate Islamic values in public schools with diverse students is both possible and effective when supported by inclusive educational strategies and strong collaboration among stakeholders. This research contributes to the discourse on religious moderation in education and provides a practical reference for other schools aiming to build inclusive, tolerant environments through curriculum and extracurricular innovation